Bi-continuous porous structures from the selective dissolution of ionic solid solutions. (1st July 2021) - Xiao, Diwen; Ke, Yubin; Wang, Congcheng; He, Chunyong; Chen, Qing
Abstract: Bi-continuous porous metal evolves from the selective dissolution of an alloy, a process known as dealloying. Here we report a similar observation in the selective dissolution of NaCl from a NaCl-AgCl solid solution. A procedure of simultaneous quenching and dissolution that retains the homogeneity of the solution is designed with the help of small-angle neutron scattering. The process in water creates bi-continuous porous AgCl of smooth ligaments and pores 300 nm wide, which can coarsen up without altering the bi-continuous morphology. Post-mortem elemental analysis identifies a NaCl-compositional threshold at 35%, below which no dissolution occurs, a critical behavior suggestive of the need for percolating dissolution pathways. The work reveals intriguing similarities between the selective dissolutions of metallic and ionic solid solutions, bridging their mechanisms and promising new ways of fabricating functional porous materials.